GIS, environmental modeling and engineering - Brimicombe, Allan (CRC Press/Taylor & Francis Group, 2010)
Promoting the critical thinking needed for the effective applications of these systems and their analytical outputs, this book explores how to use GIS and external models to solve real environmental problems. The text defines GIS, identifies how data is structured, and explains common functionality. The author discuss modeling from a neutral scientific perspective in its role of simulating phenomena, as well as from a more specific perspective in its role within environmental science and engineering. The book provides case studies and covers issues such as interoperability, data quality, model validity, space-time dynamics, and decision-support systems.